Power-velocity curve: relevance of the SRM Ergometer for simulated cycling performance and constant duration tests - Smit, A.; Wolbert, F.; Hettinga , F. J. (Journal of Science and Cycling, 2015)
Introduction: When trying to obtain cycling performance capacity, a controlled laboratory setting is required to obtain valid and reliable results [1]. Ecological validity is important, as several studies found poor agreement between lab and field time trials [2,3]. To perform realistic time trials on an ergometer, it is important that the cyclist is able to 1) choose its own cadence, 2) that the ergometer accounts for changes in kinetic energy and 3) the ergometer accounts for the non-linear relation between air-frictional forces and velocity. The SRM Ergometer has a free mode with a gear box and a big flywheel, so requirements 1 and 2 are fulfilled. It is unknown if the brake algorithm of the ergometer is linear or non- linear and how this mimics real life cycling. The aim of the present study is therefore to determine the relationship between the mechanical power output and the velocity in the SRM ergometer compared to cycling on a velodrome.